2011
DOI: 10.1891/0198-8794.31.111
|View full text |Cite
|
Sign up to set email alerts
|

Planning and Decision Making for Care Transitions

Abstract: The need to plan for future health care and residential adjustments increases with age, growing frailty, and restrictions in coverage of long-term care and will continue to grow with population aging. Older adults’ lack of financial preparation for health care costs, insufficient knowledge about available options, and inadequate communication about care-related values has become an increasing public health challenge. This chapter describes a model of Preparation for Future Care (PFC), which encompasses differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 125 publications
1
16
0
Order By: Relevance
“…When older adults are in conflict with their families about their place of care, their well-being and life satisfaction may suffer. Problem-solving theorists suggest that the ability to reach informed decisions is limited by the availability of information (Sörensen, Mak, & Pinquart, 2011;Sörensen & Pinquart, 2001). Thus, information resources for LTC decision making should define goals for care, explain the options, and provide recommendations from a diverse range of experts regarding types of LTC, benefits and risks associated with each setting, and applicability of settings to individuals' needs.…”
Section: Ltc Decision Makingmentioning
confidence: 99%
“…When older adults are in conflict with their families about their place of care, their well-being and life satisfaction may suffer. Problem-solving theorists suggest that the ability to reach informed decisions is limited by the availability of information (Sörensen, Mak, & Pinquart, 2011;Sörensen & Pinquart, 2001). Thus, information resources for LTC decision making should define goals for care, explain the options, and provide recommendations from a diverse range of experts regarding types of LTC, benefits and risks associated with each setting, and applicability of settings to individuals' needs.…”
Section: Ltc Decision Makingmentioning
confidence: 99%
“…If families do not plan ahead for caregiving, this increases the odds that decisions about caregiving will be made reactively and under pressure. For their part, adult children may experience a range of negative consequences as a result of caring for an aging parent (Sorensen, Mak, & Pinquart, 2011). Archbold (1983), for example, found that women caring for parents reported having less time and energy for their spouses and felt their freedom was restricted.…”
Section: Why Do Families Need To Talk About Future Care Needs?mentioning
confidence: 99%
“…Also worrying is the possibility that important decisions may be delegated to a child who has never been made aware of her or his parent's preferred courses of action. Children may feel overwhelmed in such circumstances (Sorensen et al, 2011), yet also be unjustifiably confident in their ability to make appropriate decisions on behalf of a loved one. Studies suggest that the choices adult children would make when acting as a proxy decision maker are often incongruent with those that their loved one would make him-or herself (Cicirelli, 1993;Zweibel & Cassel, 1989).…”
Section: Why Do Families Need To Talk About Future Care Needs?mentioning
confidence: 99%
“…In contrast, a more proactive approach to planning future housing could support older people in being more prepared and informed and help them to maintain control of their situation and the relocation process. In a study by Sorensen et al, older adults who actively planned and prepared their future care needs could more easily transition from one level of care to another, leading to better outcomes on health, overall adjustment, well-being, and fewer feelings of insecurity about the future compared to those who did not plan and prepare [13]. In contrast, lack of planning and preparation caused vital decisions to be made under crisis and time constraints [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Sorensen et al, older adults who actively planned and prepared their future care needs could more easily transition from one level of care to another, leading to better outcomes on health, overall adjustment, well-being, and fewer feelings of insecurity about the future compared to those who did not plan and prepare [13]. In contrast, lack of planning and preparation caused vital decisions to be made under crisis and time constraints [13]. Lindquist and coworkers showed that planning behavior increased for those who used the web-based portal Plan Your Life Span, focusing on planning and preparing for eventual healthrelated events during old age [14].…”
Section: Introductionmentioning
confidence: 99%